Upaya Peningkatan Akses Keadilan Terhadap Penerima Bantuan Hukum di Indonesia Melalui Paralegal - Arya Made Bayu Permana; I Putu Rasmadi Arsha Putra (Jurnal Ilmiah Kebijakan Hukum, 2023)
This article aims to examine how the development of the role of paralegals in providing legal aid in Indonesia and to examine the challenges that will be faced by paralegals in the practice of providing legal aid in Indonesia. The research method used is normative legal research with statutory and conceptual approaches. The results of this study reveal that the development of the role of paralegals in providing legal aid in Indonesia can be studied in Permenkumham No. 1 of 2018 paralegals have the authority to provide legal aid through litigation and non-litigation, but this is considered contrary to Law no. 18 of 2003 concerning Advocates, so that the Supreme Court of the Republic of Indonesia through Supreme Court Decision No. 22/P/HUM/2018 which states that the provisions of Articles 11 and 12 of Permenkumham No. 1 of 2018 does not apply in general, so that the authority of paralegals is limited to providing legal aid on a non-litigation basis, then the role of paralegals gets a reaffirmation in Permenkumham No. 3 of 2021 where paralegals are given the authority to provide legal aid through litigation but not independently, in practice providing legal aid by paralegals in general there are several challenges that can become obstacles including paralegals are required to have an understanding of the legal system, regulations and legal procedures in force in the relevant territory.